2018
DOI: 10.1186/s12879-018-3400-6
|View full text |Cite
|
Sign up to set email alerts
|

Virologic suppression in response to antiretroviral therapy despite extensive resistance within HIV-1 reverse transcriptase after the first virologic failure

Abstract: BackgroundIncomplete virologic suppression results in mutations associated with resistance and is a major obstacle to disease control. We analyzed the genotypic profiles of HIV-1 patients at the time of the first virologic failure and the response to a salvage regimen after 48 weeks.MethodsThis work was a cross-sectional, retrospective, analytical study based on data collected from medical records and genotyping tests between 2006 and 2016. The sample consisted of data on individuals living with HIV (PLWH) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
1
0
1
Order By: Relevance
“…Although M184V/I causes high-level in vitro resistance to 3TC, M184V/I is not a contraindication to continued treatment with 3TC because it increases susceptibility to AZT, and in addition, it is associated with clinically significant reductions in HIV-1 replication [14,24,25]. Similar to our study finding, a high prevalence of M184 V/I mutation has been reported in Asia, Sub-Saharan Africa and Latin America, but a lower prevalence in western Europe [26][27][28][29][30][31]. This difference can be explained by the more frequent use of 3TC in low-and middle-income countries than in West European countries.…”
Section: Discussionsupporting
confidence: 83%
“…Although M184V/I causes high-level in vitro resistance to 3TC, M184V/I is not a contraindication to continued treatment with 3TC because it increases susceptibility to AZT, and in addition, it is associated with clinically significant reductions in HIV-1 replication [14,24,25]. Similar to our study finding, a high prevalence of M184 V/I mutation has been reported in Asia, Sub-Saharan Africa and Latin America, but a lower prevalence in western Europe [26][27][28][29][30][31]. This difference can be explained by the more frequent use of 3TC in low-and middle-income countries than in West European countries.…”
Section: Discussionsupporting
confidence: 83%
“…ART aims to achieve virologic suppression (VS) in people living with HIV (PLWH). Adequate VS could prevent the development of resistance mutations, reduce HIV transmission and improve clinical outcomes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Os regimes baseados em DTG são recomendados como a melhor opção para iniciar ou como alternativa a TARV devido a sua potência e barreira genética que proporcionam rápida supressão viral, baixo potencial para interações medicamentosas, baixo risco de desenvolvimento de resistência medicamentosa, melhor tolerabilidade, menor número de comprimidos e disponibilidade como formulações em dose fixa (Cento et al, 2020). Dos indivíduos sob tratamento com ARV, estima-se que 20% trocarão as medicações devido à falha virológica (Oliveira et al, 2018). Reações adversas, falha terapêutica, interações com outros medicamentos, simplificação do tratamento, redução do custo, gravidez, ocorrência de coinfecções são exemplos de outros motivos que levam às modificações da TARV (Cesar et al, 2010;Kumarasamy et al, 2011).…”
Section: Introductionunclassified